Advances in design, simulation and manufacturing II : proceedings of the 2nd International Conference on Design, Simulation, Manufacturing: The Innovation Exchange, DSMIE-2019, June 11-14, 2019, Lutsk, Ukraine /: proceedings of the 2nd International Conference on Design, Simulation, Manufacturing: The Innovation Exchange, DSMIE-2019, June 11-14, 2019, Lutsk, Ukraine. (2019) - Unknown
No abstract available